Implementation of English Language Curriculum in Vocational Higher Education: Lecturers’ Experiences at Samarinda State Agricultural Polytechnic - Suswanto Suswanto; Yulianto Yulianto; Puspita Puspita; Budi Rachmadani (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study explores the experiences of English as a Second Language (ESL) lecturers in implementing the new English language curriculum at Politeknik Pertanian Negeri Samarinda. The research focuses on lecturers’ perceptions of the curriculum, teaching approaches, and challenges encountered in vocational higher education. A qualitative phenomenological approach was employed involving six ESL lecturers selected through purposive sampling. Data were collected through semi-structured online interviews and analyzed using thematic analysis. The findings indicate that lecturers generally perceive the curriculum positively because it promotes communicative learning, learner autonomy, and vocational relevance through English for Specific Purposes (ESP). Lecturers implemented student-centered strategies, modular teaching materials, and technology-based resources to support learning. However, the implementation faced several challenges, including limited instructional time, inadequate training, inconsistent learning materials, students’ low English proficiency, and increased workload. The study implies that effective curriculum implementation requires continuous teacher training, institutional support, improved teaching materials, and sufficient instructional time to enhance English learning outcomes and students’ communicative competence in vocational education.